TINGKAT KESUBURAN DAN REKOMENDASI PEMUPUKAN N, P, DAN K TANAH SAWAH KABUPATEN BENGKULU SELATAN - Nurmegawati Nurmegawati; W Wibawa; E Makruf; D Sugandi; T Rahman (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2012)
An alternatif way to determine soil fertility level as well as to recommend fertilizer application is by using soil test kit. The kit can measure P and K status of soils as well as the pH value. The research was aimed to evaluate soil fertility level of paddy soil and to determine fertilizer recommendation for rice (variety ? IR64) having 5 t mill-dry seeds/ha at the soil in Kedurang Ilir and Seginim, South Bengkulu. Soil samples were collected in 24 villages in the area, then they were analyzed using the Test Kit. The results showed that (1) fertility level of paddy soil in Seginim was higher than that in Kedurang Ilir, (2) there were 4 packages of fertilizer doses (250- 100-100; 200-75-100; 250-50-100; 200-100-100 kg/ha for Urea-SP36-KCl, respectively) recommended in Kedurang Ilir, (3) there were 7 packages of fertilizer doses (250-100-100; 200-50-100; 250-75-100; 200-100-75; 200-75-100; 200-100-100; 250-50-100 kg/ha for Urea, SP36, and KCl, respectively) in Seginim.Key Words: paddy soil, fertility, soil test kit